Pengaruh Hubungan Kerja terhadap Kesehatan dan Kinerja Kerja Pekerja Manufaktur - Joni Hartono; Unggul Kustiawan; Abdul Haeba Ramli; Ferryal Abadi (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2024)
This research aims to explore the influence needs status of work tipe, role conflict and temporal leadership on vigor and job performance on employement relationship. Quantitative research was carried out using Structural Equational Model (SEM) methods in 2023 with a focus on respondents working in the manufacturing sector (ceramics and the like) in Tangerang and Jakarta. Data collection was carried out randomly online use google form which resulted in 212 respondents. Respondents were dominated by men at 70% and women at 30% with a working age of 20-30 years. Research findings show that needs status have no impact on vigor worker. Role conflict shows a negative relationship to vigor and job performance, while temporal leadership shows that it only influences job performance, not vigor. This research provides managerial implications for company management that companies should manage workers, especially leaders, in several ways, including implementing a strict and selective recruitment system, as well as conducting training programs. This is so that a work system with minimal role conflict and a good temporal leadership style can be formed vigor and job performance of worker will increase as will company performance. Keywords; Needs Status, Vigor, Role Conflict, Temporal Leadership, Job Performance